British Poetry, 1900-50
IX, 228 p.
Keywords: This collection focuses on British poetry from the Georgians to the Second World War. The introduction provides the framework for the articles which follow by considering the question of the relation between poetry and society as it appears in the work of F.R. Leavis, T.W. Adorno and Antony Easthope. Written by experts, the essays cover poetic movements and individual authors, both mainstream and neglected, and address the difficult problem of making value judgements while situating poetry in its historical context.